The effect of molecular shape on oligomerization of hydrophobic drugs : molecular simulations of ciprofloxacin and nutlin - Li, Jianguo (2019)
Molecular aggregation plays a significant role in modulating the solubility, permeability, and bioactivity of drugs. The propensity to aggregate depends on hydrophobicity and on molecular shape. Molecular dynamics simulations coupled with enhanced sampling methods are used to explore the early stages of oligomerization of two drug molecules which have a strong aggregation propensity, but with contrasting molecule shapes: the antibiotic ciprofloxacin and the anticancer drug Nutlin-3A. The planar shape of ciprofloxacin induces the formation of stable oligomers at all cluster sizes. The aggregation of ciprofloxacin is driven by two-body interactions, and transferring one ciprofloxacin molecule to an existing cluster involves the desolvation of two faces and the concomitant hydrophobic interactions between the two faces; thus, the corresponding free energy of oligomerization weakly depends on the oligomer size. By contrast, Nutlin-3A has a star-shape and hence can only form stable oligomers when the cluster size is greater than 8. Free energy simulations further confirmed that the free energy of oligomer formation for Nutlin-3A becomes more favorable as the oligomer becomes larger. The aggregation of star-shaped Nutlin-3A results from many-body interactions and hence the free energy of cluster formation is strongly dependent on the size. The findings of this study provide atomistic insights into how molecular shape modulates the aggregation behavior of molecules and may be factored into the design of drugs or nano-particles.